DINAMIKA PENGALAMAN DAN MAKNA PENGGUNAAN AUGMENTED REALITY (AR) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) : STUDI KASUS DI MTS MA’ARIF - Ihda Maulidya Khothrun Nabila; Hamam Burhanuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines in depth the learning experiences of students and teachers when Augmented Reality (AR) technology is integrated into Islamic Religious Education (PAI) classrooms. Using a qualitative approach with a case study design, this research involved two PAI teachers and twelve eighth-grade students at MTs Ma'arif as the main participants. Data were collected through participatory observation, in-depth interviews, and document analysis, which were subsequently analyzed using thematic analysis techniques developed by Braun and Clarke.The findings reveal that the presence of AR has the potential to transform a "passive classroom" into a "vibrant space of exploration." AR helps students construct spatial and temporal imagination that is often difficult to achieve through printed texts alone, such as experiencing the historical depth of Isra Mi'raj or understanding the physical proportions of the Ka'bah. However, behind this enthusiasm, several dynamic tensions emerged: teachers' anxiety in operating the technology, frustration when internet connectivity was interrupted during the learning process, and careful negotiations regarding the sensitivity of visualizing religious figures.These findings emphasize that the effectiveness of AR in Islamic Religious Education does not merely lie in the sophistication of the software, but rather in how teachers manage emotions, preserve the sacredness of the material, and humanize technology itself.